The Regenerating Adult Zebrafish Retina Recapitulates Developmental Fate Specification Programs - Lahne, Manuela; Brecker, Margaret; Jones, Stuart E.; Hyde, David R. (Frontiers in Cell and Developmental Biology, 2021)
Adult zebrafish possess the remarkable capacity to regenerate neurons. In the damaged zebrafish retina, Müller glia reprogram and divide to produce neuronal progenitor cells (NPCs) that proliferate and differentiate into both lost neuronal cell types and those unaffected by the damage stimulus, which suggests that developmental specification/differentiation programs might be recapitulated during regeneration. Quantitative RT-PCR revealed that developmental competence factors are expressed following photoreceptor damage induced by intense light or in a genetic rod photoreceptor cell ablation model. In both light- and NMDA-damaged adult zebrafish retinas, NPCs, but not proliferating Müller glia, expressed fluorescent reporters controlled by promoters of ganglion (atoh7), amacrine (ptf1a), bipolar (vsx1) or red cone photoreceptor cell competence factors (thrb) in a temporal expression sequence. In both damage paradigms, atoh7:GFP was expressed first, followed by ptf1a:EGFP and lastly, vsx1:GFP, whereas thrb:Tomato was observed in NPCs at the same time as ptf1a:GFP following light damage but shifted alongside vsx1:GFP in the NMDA-damaged retina. Moreover, HuC/D, indicative of ganglion and amacrine cell differentiation, colocalized with atoh7:GFP prior to ptf1a:GFP expression in the ganglion cell layer, which was followed by Zpr-1 expression (red/green cone photoreceptors) in thrb:Tomato-positive cells in the outer nuclear layer in both damage paradigms, mimicking the developmental differentiation sequence. However, comparing NMDA- to light-damaged retinas, the fraction of PCNA-positive cells expressing atoh7:GFP increased, that of thrb:Tomato and vsx1:GFP decreased, and that of ptf1a:GFP remained similar. To summarize, developmental cell specification programs were recapitulated during retinal regeneration, which adapted to account for the cell type lost.